Energy Consumption and Low Carbon Initiatives in an Academic Building: A Case Study in Malaysia - Ilham, NI; Hussain, MZ; Abd Rahman, NH; Mat Saat, EH; Firdaus, S; Amalina, MN; Hasanuzzaman, M (International Journal of Engineering and Technology, 2018)
Climate change due to the enormous energy consumption and emission of CO2 has become major issues in the aspect of political and scientific. In Malaysia, energy consumption in building sector contributes almost half of the electricity generated hence increasing the CO2 emission. Through the Energy Efficiency Projects on Energy Efficiency (EE) programmes (2016 – 2020) initiated in RMK11,   several buildings in Malaysia have started many ways to improve energy-efficiency and saving in building such as nearly Zero Energy Building (nZEB), apparatus standard, and labeling. Less attention and awareness to energy audits and in-depth monitoring in Malaysian public universities correspondingly leads to higher energy usage. By monitoring the energy consumption pattern, the conservation can be strategies and implemented. Through this study, a preliminary investigation on the energy consumption and Building Energy Use Index (BEI) in one of the selected academic buildings in Malaysian public universities has been carried out. From an initial data collection or walk-through audits, several energy-saving suggestions were made at identified areas that can be improved towards energy saving.     Several works of literature have been reviewed to gathered additional information related to energy policies and regulations on Malaysia’s perspective.